F-box protein Fbx23 acts as a transcriptional coactivator to recognize and activate transcription factor Ace1. - Zhongjiao Liu; Kexuan Ma; Panpan Zhang; Siqi Zhang; Xin Song; Yuqi Qin (PLoS Genetics)
Protein ubiquitination is usually coupled with proteasomal degradation and is crucial in regulating protein quality. The E3 ubiquitin-protein ligase SCF (Skp1-Cullin-F-box) complex directly recognizes the target substrate via interaction between the F-box protein and the substrate. F-box protein is the determinant of substrate specificity. The limited number of identified ubiquitin ligase-substrate pairs is a major bottleneck in the ubiquitination field. Penicillium oxalicum contains many transcription factors, such as BrlA, CreA, XlnR, and Ace1, conserved in filamentous fungi that regulate the fungal development and transcription of (hemi)cellulase genes. Transcription factor Ace1 (also known as SltA) positively correlated with fungal growth and conidiation and negatively correlated with the expression of (hemi)cellulase genes. A ubiquitin ligase-substrate pair, SCFFbx23-Ace1, is identified in P. oxalicum. Most of PoFbx23 is present in free form within the nucleus. A small portion of PoFbx23 associates with Skp1 to form PoFbx23-Skp1 heterodimer or assembles with the three invariable core components (Skp1, Cul1, and Rbx1) of SCF to form the SCFFbx23 complex. Under glucose signal, PoFbx23 absence (Δfbx23) results in decreased transcription levels of the brlA gene which encodes the master regulator for asexual development and six spore pigmentation genes (abrB→abrA→aygB→arpA→arpB→albA) which encode the proteins in the dihydroxynaphthalene-melanin pathway, along with impaired conidiation. Under cellulose signal, transcription levels of (hemi)cellulase genes in the Δfbx23 mutant are significantly upregulated. When PoFbx23 is present, PoAce1 exists as a full-length version and several low-molecular-weight degraded versions. PoAce1 has polyubiquitin modification. Deleting the Pofbx23 gene does not affect Poace1 gene transcription but results in the remarkable accumulation of all versions of the PoAce1 protein. Accumulated PoAce1 protein is a dysfunctional form that no longer binds promoters of the target gene, including the cellulase genes cbh1 and eg1, the hemicellulase gene xyn11A, and the pigmentation-related gene abrB. PoFbx23 acts as a transcriptional coactivator, recognizing and activating PoAce1, allowing the latter to regulate the transcription of target genes with different effects (activating or repressing) under different signals.